Causes of stress among employees in ABC Sdn Bhd / Ahmad Fadzuli Ali ... [et al.] - Ali, Ahmad Fadzuli; Wan Ismail Edruce, Sharifah Zaaimah; Ngadis, Anisah (2007)
Initial investigation has shown that company ABC Sdn Bhd is currently facing problems in terms of human capital. The information that we obtained from internal sources point out that stress is the main reason behind this condition. Turnover rate that has suddenly skyrocketed since 2004 also has justified the need for this study. The purpose of this study is to determine the major factors that cause of stress that exist in the company and to propose ways that can mitigate it. This study was carried out using structured questionnaires to collect primary data from a sample size of 160 respondents. Interviews were also done to further validate the result of the questionnaires. In addition, TOWS matrix was used as part of the tools to identify appropriate strategies that can be used for recommendation. From the study it was found that financial and career development, uncertainty on the business continuity of the company and unclear direction from the management to the employees are the major problems that may causes stress in this company. Based on the findings, proposed strategies that focused on approaches that can be used to mitigate the three major problems was recommended.